DISTRIBUSI PENDAPATAN DI INDONESIA Proses Pemerataan Dan Pemiskinan - Didit Purnomo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
This article presents the issue of income disparities, especially the phenomenon in Indonesia. Generally, the wealth of a country could be analyzed by its GDP rate so the society's income distribution of the country is able to be analyzed also. The disparities is still occurred in Indonesia. The empirical data shows that there's a lot of disparities among regions, especially between West side of Indonesia and East side of Indonesia.A few questions appeared consider these realities, is the development move forward or backward ? Is it straight to equality or poverty ?